Anatomical Study of Leaf Characteristics of Some Plants Growing in Polluted and Non-Polluted Soils in Kirkuk City - Ibrahim, Hiyam Jamal (American Journal of Biology and Natural Sciences, 2025)
Environmental pollution decreases the growth rate of trees and shrubs, and may even result in the decline of whole forest stands. To a large extent this may be due to soil pollution, which has a negative effect on the development of root systems, especially in long-lived organisms, such as trees. Therefore, the current study aims to study the characteristics of the leaves of some plants growing in polluted and unpolluted soils. The study samples were collected from two different locations: The North Oil Company, an area contaminated with petroleum derivatives, and Kirkuk University, an uncontaminated area, for the period from November to December 2024. the results showed some anatomical characteristics of leaves of plants that were taken from an area with polluted soil, North Oil Company, where it is noted that the thickness of the leaf was the highest in eucalyptus, reaching 680 mm, while the minimum thickness was 200 mm in the mulberry plant. As for the vascular cylinder, it reached 600 mm in the eucalyptus plant, while the minimum size was in La Niña, reaching 250 mm. The epidermis reached the highest thickness of 50 mm in the mulberry plant and the minimum thickness in the eucalyptus plant. As for the cortex, the highest thickness was 160 mm in the La Niña plant and the minimum thickness in the eucalyptus, reaching 28 mm. Figures (1-10) also show the anatomical characteristics of each plant. These results were different from those of plant leaves taken from healthy soil. On the other hand, it is noted that in the La Niña leaves collected from polluted soil, the number of pores was 12, while it was 15 in the La Niña leaves collected from healthy soil. Likewise, for eucalyptus, the number of pores in the leaves of polluted soil was 22, while it was 50 in the leaves collected from healthy soil. In the mulberry leaves collected from polluted soil, the number of pores was 20, while it was 40 in the leaves collected from healthy soil. In the Citrus aurantium leaves collected from polluted soil, the number of pores was 20, while it was 32 in the leaves collected from healthy soil. Based on the results of the current study, it appears that soil contamination, especially with phytochemical derivatives, led to changes in the anatomical characteristics of the leaves of the study plants compared to leaves collected from plants growing in healthy soil.